Revisiting the Material Development of The Quran: A Quranic Study of Keith E. Small's Book of Divine Encounter - Fitri, Annisa; Shidqon, Alfan; Rahmati Nuzuliyah, Wilda (Institut Ilmu Al-Qur'an (IIQ) An-Nur Yogyakarta Komplek PP An Nur Ngrukem PO BOX 135 Bantul 55702 Yogyakarta Tlp/Fax (0274) 6469012. http://jurnalannur.ac.id/, 2023)
Throughout history, the Quran underwent physical transformations that reflected the development of society and technology. The book